Engaging and Empowering Community Resource Organizations (CROs) Before, During, and After Disasters - Angela B. Lindsey; Samantha Goldenberg (EDIS)
The role of community organizations before, during and after a crisis. Working collaborating with these groups before a disasters can increase community resilience.